"Is this to be an empathy test?": Autism and neuroqueer expression in Blade Runner (1982). (1st June 2022) - Hartley, David
Abstract : Through the explorations of a "neuroqueer" framework, the recent publications of Remi Yergeau's Authoring Autism (2018) and Julia Miele Rodas Autistic Disturbances (2018) have moved critical autism studies towards radical new considerations of the poetics and aesthetics of autistic expression in popular culture. This paper contends that such an "autistic poetics" finds a productive partnership with fantastical cinema via narratives which openly explore neurological difference, and an audiovisual aesthetic which attends to sensory pleasures and intensities. Ridley Scott's dystopian classic Blade Runner (1982) is reexamined in these autistic terms, where the cyborg characters are reconfigured as neuroqueer subjects, and the postmodern spectacle is reimagined as the empathetic core of a pro-disability message. The article concludes by asking new questions of the potential that fantastical imagining has as a rich arena for neurodivergent expression and identity.